Sistem Kemitraan Usaha Pariwisata Berbasis Pemberdayaan Masyarakat Sebagai Wujud Perekonomian Kerakyatan - Harini, Oneng Setya; Morena, Mochammad Rian Ahdian (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
This research aims to examine the role of community business partnerships in empowering Small and Medium Enterprises in the tourism sector, with a focus on the role of Community Business Partner Groups and Tourism Awareness Groups in opening market access and capital. The method used is case study analysis, including domestic cases in Surabaya. For example, Pokdarwis succeeded in marketing the ex-local Dolly hair oil product to penetrate the UK market. In addition, the collaboration between local arts and culture groups and the Ciputra group in tourism arts shows how cultural integration can increase tourist attractions. This research also includes an international study in Madagascar, where a local community partnership with the NGO Fanamby in the Anjozorobe-Angave Protected Area ecotourism has had a positive impact on conservation and economic well-being. The research results show that this partnership helps balance competition between SMEs, prevents exploitation, and facilitates SMEs to connect with large industrial supply chains. In conclusion, structured collaboration between Pokdarwis, KMUM, banking institutions and the BUMN Creative House is very important to support the sustainability of SMEs in the tourism sector. It is recommended that the government increase training and partnerships to expand economic opportunities and strengthen the regional economy. Keywords: community business partnerships, empowerment of tourism SMES, tourism awareness groups, creative house of state-owned enterprises, sustainable economy